Comparison of microbial community structure in a biological nutrient removal process at various stages of operation - Demir, Neslihan Manav; Debik, Eyup; Ozkaya, Bestami; Coskun, Tamer (DESALINATION PUBL, 2016)
In this study, the modified five-stage Bardenpho process was used for the treatment of domestic wastewater in a pilot-scale reactor with an active volume of 8.6m(3). The hydraulic retention time of the process was 16h and the sludge retention time was 15d. The removal efficiencies for chemical oxygen demand, total Kjeldahl nitrogen, ammonia nitrogen (NH3-N), total phosphorus, phosphate phosphorus (PO4-P), suspended solids, and volatile suspended solids were obtained as 87 +/- 5%; 86 +/- 12%; 93 +/- 14%; 89 +/- 9%; 88 +/- 8%; 94 +/- 4%, and 94 +/- 4%, respectively. The microbial community was also determined in the process by PCR-DGGE-Sequencing molecular techniques. While Nitrosomonas sp., Nitrosospira sp., Nitrosomonas europaea, Dechloromonas sp., Candidatus Accumulibacter sp., Bacteroidetes bacterium, Firmicutes were observed during the start-up period, Nitrosomonas sp., Nitrosospira sp., N. europaea, Dechloromonas sp., C. accumulibacter sp. were observed after the steady-state period.
Keywords: Biological nutrient removal; Community structure; Domestic wastewater; Modified Bardenpho; MUNICIPAL WASTE-WATER; DENITRIFYING PHOSPHORUS REMOVAL; ACTIVATED-SLUDGE; BACTERIAL COMMUNITY; TREATMENT-PLANT; ACCUMULATING ORGANISMS; CARBON-SOURCES; SEWAGE; PERFORMANCE; ECOPHYSIOLOGY; Engineering; Water Resources